Case report: Successful outcome of a young patient with rhabdomyolysis and shock caused by diquat poisoning - Chen, Yunchao; Ou, Zejin; Zhang, Ruichang; Long, Zhenhong; Fu, Rushen; Tang, Shihao; Wang, Zhi (Frontiers in Medicine, 2023)
The widespread use of diquat as a substitute for paraquat has led to an increase in poisoning deaths. Successful case of diquat poisoning complicated with rhabdomyolysis and shock was lack. A 13-year-old previously healthy girl ingested 40 ml of diquat solution in a suicide attempt. The concentration of diquat in serum was 436.2 ug/L at 10 hours after poisoning. The clinical course was characterized by progressive multi-organ dysfunction, particularly rhabdomyolysis and shock. The main treatments included intensive hemoperfusion combined with continuous renal replacement therapy (CRRT), drainage, and activated carbon adsorption. Meanwhile, accurate dilatation under the model of pulse indicator continuous cardiac output (PICCO) was essential for the successful treatment of shock. The serum concentration of diquat declined to 20 ug/L after 96 hours of treatments. The patient was discharged from the hospital after 3 weeks of treatment without obvious symptoms. So far, this was the first successful case of diquat poisoning complicated with rhabdomyolysis and shock, which would enrich the experience of diquat poisoning treatment.